Mechanistic insights into Nrf2-driven pathogenesis and therapeutic targeting in spinal cord injury - Tao Xie; Tao Xie; Jiyu Xu; Xinyu Liu; Yaquan Yu; Yang Lu; Tao Wang; Feng Gao; Hui Yuan; Hui Yuan (Frontiers in Immunology)
Spinal cord injury (SCI) is a traumatic disease of the central nervous system that can result in significant tissue damage and neurological dysfunction. The pathophysiological process of SCI encompasses both primary and secondary injuries, involving various pathological mechanisms such as oxidative stress, inflammation, autophagy, ferroptosis, and mitochondrial dysfunction. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a neuroprotective transcription factor intricately linked to these pathological processes. Upon exposure to external stimuli, Nrf2 undergoes increased nuclear transcription, regulating the expression of various antioxidant genes and directly modulating genes associated with the aforementioned pathological mechanisms to counteract the resultant alterations. Substantial evidence suggests that Nrf2 may be a potential therapeutic target for SCI. Activation of the Nrf2-related signaling pathway effectively inhibits neuronal death following SCI and promotes the recovery of multiple neurological functions. This review provides an overview of recent research on SCI, examines the physiological roles and mechanisms of Nrf2 in SCI, and explores therapeutic strategies targeting this signaling pathway, including non-coding RNAs, natural and synthetic compounds, and other treatments for SCI.